The spiritual mentality profile of female pietists on the South African frontier, 1750-1860 - A. W. G. Raath (Acta Theologica)
The reading of female religious literature on the South African frontier allows us to reconstruct important elements of a shared religious mentality profile of these pioneer female believers. Such a  reconstruction of the religious mentality profile of pietistic women on the frontier reveals a number of important aspects for understanding their spiritual life: self-awakenings and conversions; self-purification; self-illumination and mystically tainted experiences; recollection and the experience of quiet; meditation, contemplation, ecstasy and rapture; spiritual desertion, and abandonment of the soul and the unitive life with God in Christ.